PENERAPAN STRATEGI PEMBELAJARAN PARTISIPATORI LEARNING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Moch. Subekhan (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2020)
Learning is an important part in the transformation of knowledge in both formal and non-formal education. As time goes by and the learning process still faces various problems in the field. Among those problems is related to the use of learning strategies by a teacher. The use of learning strategies should be able to increase learning motivation, but there are many uses of learning strategies that can not increase student motivation. From here the researchers tried to implement participatory learning strategies to increase student learning motivation in Islamic Religious Education subjects. The formulation of the problem in this study is how the effectiveness of the implementation of Participatory Learning Learning Strategies in Improving Student Learning Motivation in Islamic Religious Education Subjects in Pontang 1 Junior High School. While the purpose of this study is to describe the Effectiveness of Implementing Participatory Learning Strategies in Improving Student Learning Motivation in Islamic Religious Education Subjects. This research was conducted at Pontang 1 Junior High School. The research approach used in this study uses a qualitative approach while the research method used is a descriptive qualitative method. Data collection techniques used were observation, interviews and documentation. Data analysis using the Miles and Huberman model, which is an interactive analysis model. The steps of analysis include data reduction, data presentation and conclusion. The informants in this study are the principal, teachers of Islamic education subjects and students. In the process of carrying out this research there were 6 stages that were passed. The stages are as follows: 1) The stage of fostering familiarity, 2) The stage of identifying needs, resources, and possible barriers to learning, 3) The stage of formulating learning objectives, 4) The stage of preparing learning activities programs, 5) The stage of implementing learning activities and 6) Stage of assessment of the process and results of learning activities. The results of this study indicate that the application of this learning strategy is less effective for learning Islamic Religious Education subjects. students do not have a high motivation to learn so, in learning many students do not pay attention to the material. So that the application of this learning strategy is less effective students are less interested and less motivated to learn Islamic Religious Education because the material has already been obtained.